NaOH-MODIFIED ACTIVATED CARBON FROM CORNCOBS AS A HETEROGENEOUS CATALYST: SYNTHESIS AND APPLICATION IN ULTRASOUND-ENHANCED TRANSESTERIFICATION OF USED COOKING OIL - Santana, Rosanina Kartika; Aliyatulmuna, Adilah; Nazriati, Nazriati; A'yun, Amalia Qurrata (Department of Chemistry Faculty of Science and Technology UIN Walisongo, 2025)
Biodiesel is an alternative fuel composed of fatty acid methyl esters that can be synthesized from renewable sources and offers lower combustion emissions compared to fossil fuels. In this study, biodiesel was produced via a transesterification reaction using a basic heterogeneous catalyst derived from corncob carbon, which was activated and surface-modified with NaOH to create active catalytic sites. XRD and FTIR analyses confirmed the presence of Na₂CO₃ and Na₂O, while SEM-EDX revealed a porous surface morphology with uniformly distributed sodium. Used cooking oil (UCO) served as the triglyceride source after undergoing degumming, neutralization, and adsorption processes to reduce free fatty acid (FFA) content. The transesterification reaction was conducted in an ultrasonic water bath using the reflux method at 60°C with an oil-to-methanol molar ratio of 1:12. The optimum reaction conditions were achieved using 0.5 wt% catalyst and a reaction time of 120 minutes, yielding 73.15% biodiesel. The quality of the biodiesel produced under optimum conditions was evaluated based on density, viscosity, acid value, and calorific value, which were 857 kg/m³, 3.8743 cSt, 0.2504 mg KOH/g, and 11,168 cal/g, respectively. These values comply with the quality requirements specified in SNI 04-7182-2015. GC-MS analysis confirmed that the major components of the biodiesel were methyl oleate and methyl palmitate. The utilization of corncob waste as a sustainable catalyst support, combined with alkali modification and ultrasonic enhancement, offers improved catalytic efficiency under mild operating conditions. This eco-friendly catalyst demonstrates strong potential for green catalytic processes in renewable energy development.